Media dan Perilaku Pemilih Pemula pada Pilihan Presiden Tahun 2014 di Kabupaten Sidoarjo - Totok Wahyu Abadi; Ridlaty Ayu Oktaviana Putri (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this study explained socialization was conducted by electoral commission Sidoarjo Regency and media that is used by the community and its influence on behavior of beginning voters. The basic concept of this research used theory of voter behavior and socialization of psychological aspects as well as theory of media usage. Data collection was done by distributing questionnaires to 99 beginner voter respondents as well as interviews with regional commissioners. Data analysis was performed multiple linear regression analysis and description. The results showed that the socialization conducted by electoral commission Sidoarjo Regency Sidoarjo was optimal. Media used for socialization included television, social media (internet), radio, billboards, print media (newspapers and magazines), and workshops / seminars / working meetings. Newbie voters in 2014 presidential elections indicated behavior to participate in presidential elections. The use of communication media and socialization of presidential candidates and vice presidential candidates had an influence on the behavior of novice voters. The influence of these two variables on the beginner behavior is shown by R coefficient of 27.1%. While, the most influential factor on behavior is the media used by novice voters to obtain information, knowledge, and understanding of the presidential candidate.